Association of Growth Velocity with Insulin-Like Growth Factor-1 and Insulin-Like Growth Factor Binding Protein-3 Levels in Children with a Vegan Diet - Arie Purwana; Budiono Budiono; Jose RL Batubara; Muhammad Faizi (Faculty of Medicine, Diponegoro University, 2020)
Background: The vegan diet in children provides the benefit of reducing the risk of being overweight and improving the fat profile. The risk that can occur in the provision of a vegan diet in children is anthropometric size below reference and low caloric intake. Growth hormone (GH) and Insulin like Growth Factors (IGFs) are powerful stimulators for longitudinal growth of bone and require insulin-like growth factor binding protein (IGFBPs) which acts as a transport protein for IGF-1. A vegan diet with lower calorie intake in children has lower IGF-I levels than children with an omnivorous diet.Objective: Examining the effect of vegan diets on IGF-1 levels, IGFBP-3 levels, and growth velocity.Methods: This study was done with a prospective cohort design. The study subjects were divided into two groups, namely the vegan group and the omnivorous group, then matched based on age and sex. During the study, anthropometric data collection, IGF-1 and IGFBP-3 levels measurements were done in both vegan children and omnivorous children.Results: During 6 months of observation, 22 subjects were divided into two groups, namely children with a vegan diet and children with an omnivorous diet. IGF-1 (ng / mL) in vegan children was 105.5 ± 47.3 compared to 102.7 ± 42.3 in omnivorous children with a value of p = 0.89. IGFBP-3 (ng / mL) in vegan children was 2146.4 ± 595.1 compared to 2142 ± 609.1 in omnivorous children with value of p = 0.99 and Growth Velocity (cm / 6 months) was 3.0 in vegan children (1.0-5.30), and 3.2 (2.6-6.5) in omnivorous children with value of p = 0.41.Conclusion:Children with vegan diet had IGF-1 level, IGFBP-3 level, and growth velocity that were the same as children with an omnivorous diet.